Collective Bargaining and The Public Interest: A Welfare Economics Assessment - Craig, Alton (Relations industrielles / Industrial Relations, 1991)
The article reviews the book, "Collective Bargaining And The Public Interest: A Welfare Economics Assessment," by David M. Winch.
Keywords: Arbitration; Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Collective bargaining; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Welfare economics